2021
DOI: 10.1186/s12882-021-02530-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive investigation of early kidney damage in streptozotocin-induced diabetic rats by intravoxel incoherent motion diffusion-weighted (IVIM) MRI

Abstract: Background The current study investigated the performance of intravoxel incoherent motion diffusion (IVIM) technology in monitoring early renal injury in streptozotocin rats. Methods Forty-eight Sprague-Dawley (SD) rats were divided into a control group and a diabetic mellitus (DM) group. Six rats in each group were randomly selected for MR scans at four different time points (0, 4, 8, and 12 weeks). The IVIM-derived parameters (D, D*, f and ADC va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This D value change trend coincided with reversible renal cell injury post CIRI in pathology view ( Wei et al, 2019 ). Feng et al ( Feng et al, 2021 ) reported that increased D value could be related to decreased renal tubular epithelial cell edema and reduction in the tubular flow, which was similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…This D value change trend coincided with reversible renal cell injury post CIRI in pathology view ( Wei et al, 2019 ). Feng et al ( Feng et al, 2021 ) reported that increased D value could be related to decreased renal tubular epithelial cell edema and reduction in the tubular flow, which was similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have shown that functional magnetic resonance imaging (fMRI), namely, DWI, diffusion tensor imaging (DTI) and blood oxygen level-dependent MRI (BOLD), are safe, non-invasive imaging modalities capable of providing quantitative parameters to assess the change of renal microstructure and function. There are a limited number of studies concerning the use of renal quantitative BOLD imaging and DTI in early DN in humans ( 17 20 ). Hence, our aim in this study was to assess the capability of several sequences imaging texture features to detect early DN and build a diagnostic model.…”
Section: Discussionmentioning
confidence: 99%
“…Functional MRI techniques, including IVIM and ASL, offer non-invasive quantitative assessments of renal blood flow, glomerular filtration rate, and microvascular permeability in the cortex and medulla. [14][15][16][17][18][19] These methods provide additional physiological insights crucial for early detection of kidney abnormalities, lesion characterisation and treatment response evaluation, enhancing the diagnosis and management of kidney diseases. [20][21][22] In this study, we will apply IVIM and ASL MRI to examine renal capillary perfusion and microstructures in patients with TIN, a disease model for AKI.…”
Section: Discussionmentioning
confidence: 99%